Nutritional habits in high level Spanish and German swimmers - Fernández de Alba, M.C.; Mariscal, M.; Arroyo, M.; Martin, T.; Domingo, A.; Calderon, C. (Archivos de medicina del deporte, 2008)
Usually, the food is associated to the culture and customs of every country. About the consumption of fats, in most Western countries dominated the consumption of satured fatty acids (SFA) whereas in the Mediterranean Countries, the origin of fat consumed are derived primarily from monounsaturaded fatty acids (MUFA). The aim of the present work was to study the nutritional pattern of fatty acids in the elite swimmer population coming from two different cultures: German and Mediterranean. Subjects and methods: We studied seventeen Spanish and twenty one German population of both sexes, between 15 and 30 year-old (mean in Spanish of 24,65 y. and in German of 19,91 y.), and mean Body Mass Index (BMI) in Spanish of 22.8 and in Germans of 21.04. All of them were high level swimmers that were training at High Altitude Sport Training in Sierra Nevada (2320 m.). Participants were administered with a validated quantitative questionnaire (FFQ) with the food items classified by food group. Data were collected on the consumption or not of the item and the number of times it was consumed per week. Results: The present work is based on the items 93-Butter, 94-Vegetable Margarine, 95-Bacon, 96- Mayonnaise, 97- Cream, 43-Which oil do you use usually for cooking?, and 44- What kind of oil do you use in the salad? Analyses were performed with SPSS version 15.0. A significant intake in German population were the items 93-Butter (p=0,01) and 94-Vegetable margarine (p=0,008). No significant differences were observed in the item 43 (p= 0,104), although there were significant differences in the item 44 (p= 0,006), being the largest consumer of olive oil among Spanish population. Conclusion: With these results we can intuit a higher consumption of SFA in German swimmers, as benefits its central European culture. The difference between fat for cooking and fat to used in salads appears to be due that athletes do not elect the fat with which they baked, but the use in the salad. Despite everything the consumption of olive oil in this population is limited, being replaced largely by butter and other fats. In this regard, we believe that should produce a change in habits of intake of SFA (butter and other fats) in this population to achieve a healthier diet whit MUFA (olive oil).